Fenomena-fenomena yang terkait Implementasi Kebijakan Retribusi Pasar dalam menunjang Pendapatan Asli Daerah Kabupaten Pemalang terkait Peraturan Daerah Kabupaten Pemalang No. 3 Tahun 2012 tentang Retribusi Jasa Umum - Fatmala Utaminingsih; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2018)
This research aims to find out how the implementation of Market Retribution Policy in support of Pemalang Regency Local Revenue related to Regional Regulation Number 3 of 2012 concerning Public Service Levy. And to find out the phenomena that influence the Implementation of Market Retribution Policy in Pemalang Regency Regarding Regional Regulation No. 3 of 2012 concerning Public Service Retribution. Market retribution income in Pemalang Regency in 2013 - 2016 Visit fluctuations. This research was conducted at Pemalang Market, Banjardawa Market and Warungpring Market. Keywords chosen to determine the causes of fluctuating retributions. The method in this study uses directives, direct interviews with informants. Sources of data were obtained by using purposive sampling technique, sourced from informants who were understood, involved in the implementation of market retribution policies. Data analysis used in this study is a qualitative descriptive method that refers to the events that occur. The results showed that the implementation of the Market Retribution Policy in Pemalang District was not optimally optimal. This is because there are still traders who do not comply with the applicable levy rates in the Local Regulation. Fluctuating retribution income occurs because not every day sell, rainy season, market days. Officers who collect levies must be able to be firm, so that the retribution benefits are in accordance with the tariff given in the local regulation.